2018
DOI: 10.1002/bjs.10867
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pathological node status after neoadjuvant radiotherapy for rectal cancer

Abstract: Both ypT and ypN status is of prognostic significance following neoadjuvant therapy for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…The indication for liver surgery has widened regarding number and size of metastases 11 , but is limited by the need for an adequate remnant liver volume and extrahepatic disease. The importance of liver surgery specialist participation in multidisciplinary boards has been emphasized, to increase the use of curative strategies 12 -14 . Five-year overall survival (OS) rates of 40-60 per cent Age, high BMI and co-morbidity are known risk factors for poor survival in patients with colorectal cancer 22 -24 . Lymph node status of the primary tumour is a well recognized prognostic factor 25 , although preoperative chemotherapy might modify its importance 26,27 . Lymphovascular and perineural invasion have also been attributed as independent factors for survival 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…The indication for liver surgery has widened regarding number and size of metastases 11 , but is limited by the need for an adequate remnant liver volume and extrahepatic disease. The importance of liver surgery specialist participation in multidisciplinary boards has been emphasized, to increase the use of curative strategies 12 -14 . Five-year overall survival (OS) rates of 40-60 per cent Age, high BMI and co-morbidity are known risk factors for poor survival in patients with colorectal cancer 22 -24 . Lymph node status of the primary tumour is a well recognized prognostic factor 25 , although preoperative chemotherapy might modify its importance 26,27 . Lymphovascular and perineural invasion have also been attributed as independent factors for survival 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Delaying surgery for patients who presented with good clinical outcomes has gained popularity recently (7,8). It was reported that following preop-CRT in rectal cancer, persistent lymph node metastasis (LNM) was the most indicative factor of poor prognosis (9,10). In addition, yp node (ypN) positivity (metastatic lymph node detection after surgery) was revealed to be the most important prognostic factor to predict the survival of patients harboring no residual tumor (ypT0) following surgical resection (2).…”
Section: Introductionmentioning
confidence: 99%
“…We read the recent article by Duchalais and colleagues, with great interest. There are several aspects of the article with which one might take issue.…”
mentioning
confidence: 99%
“…Finally, a recent study has pointed to LN ratio as a more effective indicator of oncological adequacy in node‐positive rectal cancer compared to ypN stage. Again, no attempt was made to include both LN ratio and ypN stage in the same multivariate model in the study by Duchalais et al …”
mentioning
confidence: 99%